Konflik Batin Tokoh Tomoya Sugisaki dalam Anime Summer Ghost karya Loundraw - Bintang Bayu Putra, Agung Anom; Candra Lestari, Ni Putu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2024)
This research examines the inner conflict experienced by the character in the Anime “Summer Ghost”, the main character Tomoya Sugisaki, by Loundraw. The purpose of the research is to describe the form and inner conflict of Tomoya Sugisaki's character by using qualitative method. The theory used in this research, namely the theory of literary psychology proposed by Wellek and Warren and Psychoanalysis Theory according to Kurt Lewin. The results of this study show several forms of inner conflict experienced by Tomoya Sugisaki which include: approach-approach conflict, avoidance-avoidance conflict, and approach-avoidance conflict. One of the most prominent causes of inner conflict in Tomoya Sugisaki, which is very visible in the social relationships in the character's life, is the driving force due to the curiosity of the character about many things.